Thermodynamic and kinetic modelling of 6-gingerol scCO2 extraction - Muhamad Syafiq Hakimi Kamaruddin; Gun Hean Chong; Mohd Hafiz Abu Hassan; Norhidayah Suleiman (Elsevier BV, 2026)
This investigation delves into the kinetics and thermodynamics of the extraction of 6-gingerol from Bentong ginger using supercritical carbon dioxide (scCO2). The extraction was performed under varying pressures (15, 25, and 35 MPa) and temperatures (40, 50, and 60°C), and with various particle sizes (300, 425, and 600 µm). Kinetic models such as Peleg, First-order, and Two-site kinetic models were used to fit the experimental data. All of these demonstrated high correlation coefficients (R2 > 0.95), indicating their ability to capture the extraction behaviour, but the two-site kinetic model emerged as the most accurate, with the lowest root mean square error (RMSE) (with values ranging from 7.436 to 27.173 across the extraction conditions), and its effectiveness was further endorsed by chi-square (χ2) comparisons. Kinetic analysis using the Arrhenius equation revealed an activation energy (Ea) of 10.290 kJ/mol−1 and a pre-exponential factor of 91.37 s−1. In the realm of thermodynamics, the study uncovered key parameters: Gibbs free energy (ΔG) at −0.494 kJ/mol−1, enthalpy change (ΔH) at −19.955 kJ/mol−1, and entropy change (ΔS) at 0.062 J/mol−1, calculated at the optimal extraction temperature. These findings underscore the spontaneous and exothermic nature of 6-gingerol extraction in scCO2, which makes the process particularly efficacious at lower temperatures. The study not only elucidates the extraction mechanism but also paves the way for optimizing 6-gingerol extraction in industrial settings, considering the influence of pressure, temperature, and particle size.